2010
DOI: 10.1097/ftd.0b013e3181f0634c
|View full text |Cite
|
Sign up to set email alerts
|

The Convergence of Therapeutic Drug Monitoring and Pharmacogenetic Testing to Optimize Efavirenz Therapy

Abstract: The aim of this study was to show the benefits of combining therapeutic drug monitoring (TDM) and pharmacogenetic analyses to optimize efavirenz (EFV) therapy. Patients were selected to minimize nongenetic differences between patients: 32 HIV adherent patients without drug interactions treated with an EFV nonindividualized dose over at least 1 year and included in a TDM program were genotyped according to minimum steady-state concentrations (C ss min). The EFV plasma concentrations (n = 158) were quantified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Recently the combined use of therapeutic drug monitoring (TDM) with pharmacogenetic testing is advocated to optimize efavirenz therapy [52]. Regular TDM practice is not feasible in resource-limited countries like Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the combined use of therapeutic drug monitoring (TDM) with pharmacogenetic testing is advocated to optimize efavirenz therapy [52]. Regular TDM practice is not feasible in resource-limited countries like Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…EFV autoinduction is also influenced by a patient’s genotype; for example, patients with the CYP2B6 * 1 allele may exhibit long-term EFV autoinduction [33, 34]. In selected situations, therapeutic drug monitoring of antiretroviral therapy may help to address these issue by individualizing dosage to minimize side effects while maintaining antiviral efficacy [31, 35], although it is important to note that EFV is often co-formulated in a fixed dose as part of an anti-viral regimen, adding a layer of complexity to individualization of dosage.…”
Section: Efv-enzyme Interactions and Drug-drug Interactionsmentioning
confidence: 99%
“…It has been proposed that CYP2B6 genotyping could be used as a screen to identify individuals who may be either slow or fast metabolizers of EFV and may benefit the most from early therapeutic drug monitoring (TDM), in order to optimize dosage as a function of exposure before or during the initiation of drug therapy [35, 46]. For example, one retrospective study reported that therapeutic dose monitoring and dose reduction in 31 patients with one or two 516 T alleles from a standard 600 mg/day dose of EFV to 400 mg/day, reduced the mean EFV C min (5.7 +/−3.4 mg/l at 600 mg/day) to within therapeutic range (2.39 +/− 1.28 mg/l at 400 mg/day) [47].…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…As new ARV drugs are developed and newer techniques become more widely available, the approach to TDM in the management of HIV is constantly changing [22,64]. TDM of ART requires a multidisciplinary approach, including an infectious disease specialist, a clinical pharmacist, a TDM specialist, a virologist and in the future perhaps a geneticist, to fully integrate TDM into optimal clinical management of the individual HIV-infected patient.…”
Section: Virologic Failurementioning
confidence: 99%